2019
DOI: 10.1016/j.jpba.2019.05.062
|View full text |Cite
|
Sign up to set email alerts
|

Validation of an LC-MS/MS method for the quantitative analysis of 1P-LSD and its tentative metabolite LSD in fortified urine and serum samples including stability tests for 1P-LSD under different storage conditions

Abstract: Validation of an LC-MS/MS method for the quantitative analysis of 1P-LSD and its tentative metabolite LSD in fortified urine and serum samples including stability tests for 1P

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 16 publications
8
21
0
Order By: Relevance
“…It has since been confirmed that the 1‐acyl substituted lysergamides ALD‐52, 1P‐LSD, 1P‐ETH‐LAD, and 1B‐LSD were indeed transformed into LSD and ETH‐LAD, respectively 22,24 . These findings were also consistent with the data reported in an intoxication where the ingestion of 1P‐LSD in blotter form did not result in its detection in either urine or serum but LSD instead 23 . In the present investigation, an incubation of 1CP‐LSD with human serum also revealed the formation of LSD when the incubation mixture was analyzed by LC‐ESI single quadrupole MS. As summarized in the Supporting Information section (analyses performed in triplicate but only one representative example shown), it was found that the signal response related to the hydrolysis product increased over time when analyzed at 0, 1, 2, 3, 5, 7, and 24 h. These results showed that 1CP‐LSD was hydrolyzed to LSD in serum but that conversion was not complete within the first 24 h. However, 1CP‐LSD is likely to be hydrolyzed at a much faster rate in vivo because humans express carboxyesterase in red blood cell membranes but not in serum 37,38 .…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…It has since been confirmed that the 1‐acyl substituted lysergamides ALD‐52, 1P‐LSD, 1P‐ETH‐LAD, and 1B‐LSD were indeed transformed into LSD and ETH‐LAD, respectively 22,24 . These findings were also consistent with the data reported in an intoxication where the ingestion of 1P‐LSD in blotter form did not result in its detection in either urine or serum but LSD instead 23 . In the present investigation, an incubation of 1CP‐LSD with human serum also revealed the formation of LSD when the incubation mixture was analyzed by LC‐ESI single quadrupole MS. As summarized in the Supporting Information section (analyses performed in triplicate but only one representative example shown), it was found that the signal response related to the hydrolysis product increased over time when analyzed at 0, 1, 2, 3, 5, 7, and 24 h. These results showed that 1CP‐LSD was hydrolyzed to LSD in serum but that conversion was not complete within the first 24 h. However, 1CP‐LSD is likely to be hydrolyzed at a much faster rate in vivo because humans express carboxyesterase in red blood cell membranes but not in serum 37,38 .…”
Section: Resultssupporting
confidence: 86%
“…It was shown recently that 1‐acylated lysergamides likely serve as prodrugs to either LSD (1P‐LSD, 1B‐LSD, ALD‐52) 18,19,22–24 or N 6 ‐ethyl‐nor‐LSD (ETH‐LAD) (from 1P‐ETH‐LAD), 19,22 suggesting that the detection of the parent 1‐acylated lysergamide in vivo following ingestion might be challenging.…”
Section: Introductionmentioning
confidence: 99%
“…Little is known about the adverse effects of lysergamide designer drugs. One case of a 17-year-old male who developed anxiety, hallucinations, restlessness, elevations of blood pressure, palpitations, and tachycardia after ingesting 1P-LSD was reported (Grumann et al 2019). 1P-LSD was confirmed as an ingredient of the ingested blotter paper but could not be detected in urine or serum samples, despite being sufficiently stable in these matrices.…”
Section: Adverse Effects Of Lysergamidesmentioning
confidence: 99%
“…Recently, a number of LSD derivatives and analogues have been investigated, namely 1‐acetyl‐LSD (1A‐LSD, ALD‐52), 1‐propanoyl‐LSD (1P‐LSD), 1‐butanoyl‐LSD (1B‐LSD), N 6 ‐ethyl‐nor‐LSD (ETH‐LAD), 1‐propanoyl‐ N 6 ‐ethyl‐nor‐LSD (1P‐ETH‐LAD), N 6 ‐allyl‐nor‐LSD (AL‐LAD), N ‐ethyl‐ N ‐cyclopropyl lysergamide (ECPLA), (2′ S ,4′S)‐lysergic acid 2,4‐dimethylazetidide (LSZ), and lysergic acid morpholide (LSM‐775) (Fig. B ).…”
Section: Prodrugs Of Psychoactive Substancesmentioning
confidence: 99%
“…B ). A biotransformation has been observed in lysergamides acylated at the indole nitrogen that in turn produces the corresponding “core” drug of LSD or ETH‐LAD . Therefore, 1P‐LSD, 1B‐LSD, and ALD‐52 are all prodrugs of LSD and 1P‐ETH‐LAD is a prodrug of ETH‐LAD.…”
Section: Prodrugs Of Psychoactive Substancesmentioning
confidence: 99%